2019
DOI: 10.1088/1748-9326/aaf4d2
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle fleet turnover and the future of fuel economy

Abstract: The real-world impacts of the Trump administration's effort to roll back the Corporate Average Fuel Economy (CAFE) standards for new light-duty vehicles are not obvious, because new vehicles are highly durable and remain in the on-road fleet for many years. We demonstrate that freezing CAFE between 2020-2026, one of the proposals circulated by the Trump administration, will increase fleet fuel consumption and greenhouse gas emissions until 2040 and beyond, because relatively lessefficient vehicles sold during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…92 ). Due to long time lags of vehicle stock turnover (with vehicles lasting 15-25 years), the impacts of a freeze are especially detrimental in the long-run 93 .…”
Section: Strengthen Vehicle Emissions Standards Cut the Loopholesmentioning
confidence: 99%
“…92 ). Due to long time lags of vehicle stock turnover (with vehicles lasting 15-25 years), the impacts of a freeze are especially detrimental in the long-run 93 .…”
Section: Strengthen Vehicle Emissions Standards Cut the Loopholesmentioning
confidence: 99%
“…IHS Markit (2021) reported the average age of LDVs in operation on US roads is 12.1 years in 2021 -a 15% increase in the last decade -and is expected to continue to grow. One study that analyzed US vehicle data found that the useful life of an ICE LDV can reach up to 30 years (Keith et al, 2019). 2018).…”
Section: Interlinked Components Of True Decommissioningmentioning
confidence: 99%
“…Numerous studies have investigated the factors that influence the amount of vehicle emissions and fuel consumption and proposed control strategies accordingly. From the perspective of vehicles, technologies such as emission after-treatment and vehicle fleet electrification can lead to a substantial decrease in emissions and fuel consumption [ 4 , 5 , 6 , 7 , 8 ]. Methods that mitigate traffic congestion, such as adaptive signal timing control, countdown signal timers, predictive cruise control, and connected automated vehicles (CAVs) can also effectively control traffic emissions through shorter delays and less stop-and-go operations [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%